AIEgen-functionalised mesoporous silica nanoparticles as a FRET donor for monitoring drug delivery. Issue 3 (18th January 2017) - Wang, Duo; Chen, Jie; Ren, Li; Li, Qinglan; Li, Dongdong; Yu, Jihong
Abstract : AIEgen-functionalised mesoporous silica nanoparticles can be used for cell imaging and monitoring the drug release process by different emission colours based on the FRET mechanism. Abstract : Aggregation-induced emission luminogens (AIEgens), tetraphenylethene, were post grafted onto mesoporous silica nanoparticles to form AIEgen-functionalised mesoporous materials. The obtained blue-emitting materials can serve as a fluorescence resonance energy transfer (FRET) donor for monitoring the release process of doxorubicin hydrochloride (DOX) as an acceptor by the change of the fluorescent signal, showing potential application in imaging-guided therapy.